2020
DOI: 10.1097/md.0000000000023130
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of coenzyme Q10 supplementation on glucose metabolism, lipid profiles, and biomarkers of inflammation in women with polycystic ovary syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the common gynecological endocrine system diseases. It is characterized by excessive androgen, rare or anovulation, and polycystic ovary morphology. Coenzyme Q10 (CoQ10) is a fat-soluble natural vitamin, which has a continuous oxidation-reduction cycle and is an effective antioxidant that can protect ovaries from oxidative damage. This study aims to systematically summarize and analyze the scientific literatures on glucose metabolism index, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
3
0
2
Order By: Relevance
“…29 Hormonal profile was improved after Co-Q10 supplementations especially reduction in LH and testosterone levels. Similar results were obtained by Gouveia et al, 30 Izadi et al, 31 and Liu et al 32 A recent and lowering triglycerides by enhancing rapid lipolysis. These mechanisms support the wide CO-Q10 administration in women with PCOS.…”
Section: Resultssupporting
confidence: 86%
“…29 Hormonal profile was improved after Co-Q10 supplementations especially reduction in LH and testosterone levels. Similar results were obtained by Gouveia et al, 30 Izadi et al, 31 and Liu et al 32 A recent and lowering triglycerides by enhancing rapid lipolysis. These mechanisms support the wide CO-Q10 administration in women with PCOS.…”
Section: Resultssupporting
confidence: 86%
“…CoQ10 has a role in the regulation of blood sugar levels by improving insulin sensitivity. The administration of CoQ10 supplements can enhance glucose metabolism, leading to enhanced glycemic control among individuals with diabetes (40). Furthermore, CoQ10 functions as a potent antioxidant, thereby safeguarding the body against oxidative stress and mitigating the likelihood of experiencing diabetes problems.…”
Section: Benefits Of Coq10 In Managing Diabetesmentioning
confidence: 99%
“…A study by Izadi et al 45 showed that supplementation with CoQ 10 alone or in combination with vitamin E had considerable effects on fasting plasma glucose (FPG) and homeostasis model assessment-IR (HOMA-IR) as compared to those under the placebo treatment, whereas only co-supplementation affected sex hormone-binding globulin concentrations, which decreased total serum testosterone levels. In a meta‐analysis, Liu et al 46 concluded that CoQ 10 administration can significantly reduce FPG and HOMA-IR, and effectively improve glucose and lipid metabolism, inflammation, and sex hormone levels. Refaeey et al 47 evaluated the combined ovulation induction effects of oral CoQ 10 and CC in CC-resistant PCOS patients through a prospective randomized controlled trial, and found that clinical pregnancy rate was significantly higher in the CoQ 10 group than in the control group.…”
Section: Antioxidants In Pcosmentioning
confidence: 99%